2015
DOI: 10.1002/cjce.22317
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive experimental study and numerical simulation of vapour extraction (VAPEX) process in heavy oil systems

Abstract: There are significant heavy oil and bitumen resources in Canada. Global energy demand is rising while environmental constraints make heavy oil recovery more challenging. Therefore, looking for an economically viable and environmentally-friendly heavy oil recovery technique is essential. Recently, solvent-based heavy oil recovery techniques (i.e., VAPEX) have attracted attention due to their economic and environmental advantages over thermal methods. In this research, an extensive experimental and numerical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Later, Rezaei et al [7] showed that, unlike SAGD process, the oil-wet condition of the formation positively impacts the oil production rate. To improve the economic viability of Vapex process, Torabi et al [8][9][10] suggested injecting the noncondensable gases like CO 2 with a hydrocarbon solvent. Using numerical simulation they found out that CH 4 or CO 2 coinjection is a viable option and results in equal or greater recovery factors in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Rezaei et al [7] showed that, unlike SAGD process, the oil-wet condition of the formation positively impacts the oil production rate. To improve the economic viability of Vapex process, Torabi et al [8][9][10] suggested injecting the noncondensable gases like CO 2 with a hydrocarbon solvent. Using numerical simulation they found out that CH 4 or CO 2 coinjection is a viable option and results in equal or greater recovery factors in most cases.…”
Section: Introductionmentioning
confidence: 99%